1998
DOI: 10.1159/000027558
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Platelet-Activating Factor-Acetylhydrolase in Human Middle Ear Effusions

Abstract: Factors related to inflammation, including platelet-activating factor (PAF), apparently have a role in chronic otitis media with effusion. PAF is metabolized to the biologically inactive lyso-PAF by the enzyme PAF-acetylhydrolase (PAF-AH). We have obtained evidence that PAF-AH activity is present in human middle ear effusions in patients with chronic otitis media with effusion. The present study revealed the enzyme in human middle ear effusions to be the plasma type PAF-AH. We suggest that PAF-AH may be involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…PAF induces neutrophil adhesion to endothelial cells (137). In addition, PAF appears to play a major role in the production of MEE by increasing vascular permeability, stimulating epithelial secretory activity, and reducing the mucociliary activity of the middle ear causing eustachian tube dysfunction (140). By stimulating mucous glycoprotein release, PAF appears to be a mediator in the hypersecretion of mucus in the middle ear cavity and eustachian tube (141).…”
Section: Inflammation and Ommentioning
confidence: 99%
“…PAF induces neutrophil adhesion to endothelial cells (137). In addition, PAF appears to play a major role in the production of MEE by increasing vascular permeability, stimulating epithelial secretory activity, and reducing the mucociliary activity of the middle ear causing eustachian tube dysfunction (140). By stimulating mucous glycoprotein release, PAF appears to be a mediator in the hypersecretion of mucus in the middle ear cavity and eustachian tube (141).…”
Section: Inflammation and Ommentioning
confidence: 99%
“…With respect to biochemical properties, PAF‐AH in CSF was different from other known acetylhydrolases 2–8, 13–18. It is reported that plasma type PAF‐AH has a higher molecular weight than the intracellular type and is resistant to protease 13.…”
Section: Discussionmentioning
confidence: 95%
“…The enzyme is distributed widely in tissues and plasma and is thought to be a defense mechanism that protects the host against the toxic effects of PAF and other biologically active oxidized phospholipids. Higher levels of PAF‐AH have been found in plasma and other body fluids in a variety of different diseases,2–8 but few studies have been conducted to measure the level of PAF‐AH in cerebrospinal fluid (CSF) 7. We, therefore, measured the PAF‐AH level in CSF of children with a variety of conditions, including meningitis, to determine if it is involved in the central nervous system (CNS) defense mechanism against the injury.…”
mentioning
confidence: 99%